Numerical Modeling on Hydraulic Fracturing in Coal-Rock Mass for Enhancing Gas Drainage - Zhigang Yuan; Yaohua Shao (Advances in Civil Engineering)
The mechanism of how hydraulic fracturing influences gas drainage in coal-rock mass is still not clear due to its complex mechanism. In this work, statistical distributions are firstly introduced to describe heterogeneity of coal-rock mass; a novel simultaneously coupled mathematical model, which can describe the fully coupled process including seepage-damage coupling during hydraulic fracturing process and subsequent gas flow during gas drainage process, is established; its numerical implementation procedure is coded into a Matlab program to calculate the damage variables, and it partly uses COMSOL solver to obtain numerical solutions of governing equations with damage-flow coupling; the mathematical model and its implementation are validated for initial damage pressure and mode of a single solid model without considering flow-damage coupling, as well as fracture initiation pressure and influence of heterogeneity on damage evolution of hydraulic fracturing considering flow-damage coupling; and finally, based on an engineering practice of hydraulic fracturing with two boreholes, the mechanism of how hydraulic fracturing influences gas drainage is investigated, numerical simulation results indicate that coal-rock mass pore-fissure structure has been improved, and there would exist a gas migration channel with characteristics of higher porosity and lower stresses, which demonstrates significant effects and mechanism of hydraulic fracturing on improving coal-rock permeability and enhancing gas drainage. The research results provide a guide for operation of hydraulic fracturing and optimal layout of gas drainage boreholes.